Improving Student Learning Outcomes in Islamic Education Learning Using the Problem Based Learning Method at SD Negeri Salim Pinim - Afriani, Masdah (Jurnal Profesi Guru Indonesia, 2024)
In this research, the aim is to apply the active learning of the Problem Based Learning model or commonly known as problem-based learning, in order to improve the learning outcomes of students in Islamic Religious Education and Moral Education class IV at Salim Pinim State Elementary School. With the Problem Based Learning model, students can be actively involved in learning and this model is one of the alternatives that make learning more active, effective, creative, and enjoyable, which is expected to be able to increase the learning outcomes and student activity in Islamic Religious Education and Moral Education. This research is based on the fact that in the learning of Islamic Religious Education and Moral Education so far, teachers still use the lecture method, have not tried other methods, this has an impact on the exhaustion of students to play an active role in learning, resulting in weak student activity and learning outcomes. In learning, the teacher has not used an interesting learning model so that the student's learning process is less conducive. This research is a Class Action Research (CAR) which is carried out consisting of two cycles, and the subjects of the research are 28 students in class IV of Negeri Salim Pinim SD. The results of this research show that the active learning of the Problem Based Learning model has increased with each cycle. This is evident from the average value of student learning results for each cycle, which is 65 in cycle I and 74 in cycle II. Student learning results have increased. Based on the results of the research, it can be concluded that the application of a problem-based learning model (Problem Based Learning) can improve learning outcomes in the subjects of Islamic Religious Education and Moral Education in Class IV at Salim Pinim Elementary School.